Organizational Satisfaction and Participation: ACE Members Speak Out - LaRae M. Donnellan; Gail Snowdon (Journal of Applied Communications, 2000)
Any professional organization, such as Agricultural Communicators in Education (ACE), needs to stay relevant to the needs of its members. This article reports the results of a 1998 membership survey that examined such questions as why people belong to ACE, how well ACE is meeting member needs, what would make ACE more relevant, and whether ACE should change its name. Fifty-four percent of active members responded to an on-line survey. The top reasons given for belonging to ACE included professional development and networking with peers. However, only 47 percent of respondents felt ACE was doing "well" or "very well" in meeting members' professional development needs. The longer a person belonged to ACE, the higher he or she rated ACE overall. The challenge for ACE leadership is to provide appropriate professional development opportunities to match the high ranking given to networking, job announcements, publishing, leadership opportunities, and award recognition. ACE also needs to address the changing culture within communications offices that has resulted in changing expectations and participation.